Discontinuation or reduction in benzodiazepine use by treatment with the traditional herbal medicine Hangekobokuto, case reports - Ryo Yoshinaga; Toshinobu Maki; Yusuke Goto; Hiroki Inoue; Hiromi Yano; Eiichi Tahara (Journal of General and Family Medicine, 2020)
Abstract In this report, we present two cases in which benzodiazepines (BZDs) were able to be successfully reduced or discontinued by treatment with traditional Japanese herbal medicine (Kampo medicine), including Hangekobokuto (HKT). These two patients with long‐term use of BZDs due to mental disorders suffered epigastric symptoms. After starting Kampo therapy including HKT, their epigastric symptoms were improved and they were able to reduce or discontinue the use of BZDs. This suggests that HKT is a potentially promising substitutive pharmacotherapy for patients with long‐term use of BZDs. HKT should be considered as a treatment for patients with mental disorders who have taken BZDs for a long time and suffer from medically unexplained epigastric symptoms.